Language Assessment in Higher Education: Challenges and Consequences - Almas Ashraf، Sajida Zaki, (PJE, 2023)
Several research studies have reported that assessment at higher education institutions for English language courses in Pakistan are deficient. However, they have not addressed the challenges causing these weaknesses. The current study, therefore, is an attempt to gain insight into the reasons of and the resulting consequences of these unsatisfactory assessment practices.